Phonological and contextual factors affecting voice quality in Dinka vowels - Bazoukis, Georgios (The University of Edinburgh, 2012)
Dinka language is Nilotic language with rich and complex suprasegmental and morphological system that has not been investigated fully yet. Furthermore, voice quality is a linguistic notion that is also understudied in its phonological and phonetic sense. This paper is concerned, primarily, with investigating the relationship between breathy voice with Dinka vowels and, secondarily, with whether there is an actual association between certain voice qualities and certain tonal patterns in Dinka language. In order for this investigation to take place a large volume of Dinka utterances dataset is employed. Firstly, the data was quantified and, secondly, some appropriate scripts were utilized for the calculation and extraction of the desired values. The statistical analyses of the findings have showed that there are some strong correlations between certain voice qualities and tones as well as that some phonetic properties are more reliable as acoustic correlates of breathiness than others. In the end, this paper establishes a new understanding of the aforementioned goals and to some extend assesses the applicability of the scripts to other similar studies.
Keywords: Dinka language; Voice quality; Praat scripts